Modelling of radiation propagation in a photonic integrated circuit based on a polymer waveguide and phasechange material nanoparticles - V.V. Ionin; V.A. Mikhalevsky; A.A. Burtsev; A.V. Kiselev; A.A. Nevzorov; N.N. Eliseev; A.A. Lotin (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2024)
This paper presents the results of numerical modelling of optical radiation propagation in a SU-8 polymer waveguide and signal modulation at different phase states of an array of nanoparticles of the phase-change material Ge2Sb2Te5 (GST). It is shown how the transmitted radiation is modulated for different numbers of nanoparticles when placed on the top and at the edge of the waveguide. The simulation results show that in addition to the influence of the phase states (crystalline or amorphous) on the properties of the transmitted signal, in the case of nanoparticles not only reflection and absorption but also scattering of the material play a prominent role. The basic possibility of controlling the optical signal of telecommunication range passing through the interface by switching the optical active element based on nanoparticles of phase-change material is demonstrated. The concept of developing photonic integrated circuits proposed in this work is the cheapest of all known planar technologies of developing waveguide devices and allows realizing computing elements and architectures on its basis with a high degree of heterogeneous integration.